Faktor Penentu Keputusan Hedging pada Perusahaan: Sebuah Studi Literatur - Andria Indah Maharani; Atika Jauharia Hatta; Frasto Biyanto (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
Hedging as an effort to protect against foreign exchange rates, plays an important role for companies active in international trade, especially to overcome exchange rate risk (currency risk). However, until now the level of hedging use is still relatively low, this is due to hedging not always providing optimal profits for the company and a lack of understanding regarding the factors that influence hedging decisions. The aim of this research is to find out what factors will influence a company's hedging decisions. The research uses qualitative methods by reviewing 30 previous articles that examine the factors that influence company hedging decisions. The articles reviewed came from within and outside Indonesia, published between 2010 and 2023. The articles used were articles indexed by Sinta (Science and Technology Index) and Scopus. This research found 26 factors that can influence a company's hedging decisions, with the most widely used theories being shareholder value maximization theory, pecking order theory, portfolio theory, and trade-off theory. The research results show that the factors that have the most significant influence on a company's hedging decisions are company size, liquidity and profitability. This research not only helps identify factors that influence hedging decisions, but also helps readers find research gaps for subsequent research.